Characterization of Sugar Beet Pulp Modified with Phosphoric Acid and its Use in Removal of Colored Matters and Cations from Thin Sugar Juice - Turk, Feride N.; Arslanoglu, Hasan; Tumen, Fikret (Springer India, 2023)
In this study, it has been determined that the cation removal capacity of the modified sugar beet pulp obtained by saponification with sodium hydroxide and esterification with phosphoric acid increased, and it provides significant color lightening and cation removal when contacted with thin sugar juice under suitable conditions. Although both the acidic and neutralized forms of this material show similar activities, the use of the neutralized form reduces the risk of inverting the sugar in the thin sugar juice. Sugar beet pulp was modified, and some properties were determined. Sugar beet pulp become more stable when modified with phosphoric acid. To reduce the amount of molasses, it is appropriate to use the material in an acid form together with an anion exchanger. It has advantages, such as the modification of sugar beet pulp with phosphoric acid can be done in sugar factories.
Keywords: Sugar beet pulp; Phosphoric acid; Modification; Thin sugar juice; Decolorization